ANALISIS PERBANDINGAN MODEL SPRINGATE, ZMIJEWSKI, DAN ALTMAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diana Supriati; Icuk Rangga Bawono; Kusriyadi Choirul Anam (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
Financial Distress can be interpreted as a phase of the decline in financial conditions experienced by a company. One of the indicators is the inability of the company to pay off its debts that are due, which is caused by losses suffered by the company in several years. This study aims to analyze and predict financial distress in companies listed on the Indonesia Stock Exchange that have suffered for several years and to find out which prediction models can indicated the best financial distress. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The sample in this study was determined based on the purposive sampling method and obtained a sample of 16 companies, the final observation in this study were 48 observations. The data in this study were analyzed using the Springate, Zmijewski, and Altman models. This study concludes that for sample analyzed by the Springate and Altman models, the majority are classified as having indicated financial distress and for those analyzed by the Zmijewski model only a small proportion classified as having financial distress. Furthemore, for the best predictive model in indicating financial distress is the Springate model